Consultoria colaborativa à distância em tecnologia assistiva para professores de salas de recursos multifuncionais - Calheiros, David dos Santos (2015)
The implementation of Assistive Technology resources (AT) can make a big difference in the education of students with disabilities. However, the continued use of these by specialist teachers is considered challenging, for though they take ownership of knowledge about assistive technology, when they are submitted to continuing education programs, in general do not give continuation to the use of these resources when completed such training. Considering the recommendation of the literature of a permanent service of collaborative consulting AT for teachers of students with disabilities, the objective of this study consist to plan, implement and evaluate a service of collaborative consulting at distance in Assistive Technology for teachers of Multifunction Resources Room (MRR) from their demands. The study developed in the qualitative approach, was exploratory type. The participants were six teachers of MRR and three consultants in the area of Special Education. The datas were colleted through the activities realized in a Virtual Learning Enviroment (VLE) through it too were obtained responses to the questionnaires (involving open and closed questions). Initially, was identified the demand for AT knowledge of the participant teachers and the possibility of collaborative consulting. Then, the intervention was based on the provision of the service of collaborative consulting in distance mode and each teacher chose a case of a student with cerebral palsy (CP) that demanded the Assistive Technology. After the intervention by collaborative consulting in AT in the modality at distance, occurred the process of assessing the actions of these provided service. The results obtained through of the posting in the VLE and of the responses to open questions of the questionnaires were treated by the technique of content analysis, especially the thematic. In relation to the data of closed questions of the questionnaires, too was realized a descriptive analysis through absolute frequencies. Generally speaking, the evidences found indicate that is possible to identify at distance the demands of teachers about the AT use as well as to plan and implement action of collaborative consulting from VLE. The collaborative consulting service proposed in this investigation, it was revealed still beneficial to the professional performance of consultants and teachers of the research. The students with CP selected by teachers for the study in the consulting service too were benefited through implemented actions. However, they were not the only ones blessed, since the consulting also allowed to solve educational problems of other students through teacher empowerment. Thus, the contribution of this research to the scientific literature is to indicate a further possibility of support service for inclusive school in order to solve educational problems in the AT.